Rifampicin Attenuated Global Cerebral Ischemia Injury via Activating the Nuclear Factor Erythroid 2-Related Factor Pathway - Chen, Beibei; Cao, Huimin; Chen, Lili; Yang, Xuemei; Tian, Xiaoyan; Li, Rong; Cheng, Oumei (Frontiers in Cellular Neuroscience, 2016)
Background: Recent studies have found that rifampicin has neuroprotective properties in neurodegenerative diseases. However, the exact mechanisms of action remain unclear. The nuclear factor erythroid 2-related factor 2 (Nrf2) has been considered a potential target for neuroprotection. In this study, we examined whether rifampicin exhibits beneficial effects mediated by the Nrf2 pathway after global cerebral ischemia (GCI). Methods: Rats were randomly assigned to four groups that included a sham group and 3 treatment groups with global ischemia-reperfusion [control, rifampicin and rifampicin plus brusatol (an inhibitor of Nrf2)]. Rats were subjected to transient GCI induced by bilateral common carotid artery occlusion for 20 min with systemic hypotension by blood withdrawal. The Morris water maze test was performed for neurobehavioral testing, whereas the pathological changes were investigated using HE and TUNEL staining. The protein expression of Nrf2, hemeoxygenase-1 (HO-1) and cyclooxygenase-2 (COX-2) in the hippocampus were analyzed by Western blotting. The immunofluorescence staining was used to determine the distribution of Nrf2. Results: Rifampicin treatment significantly improved spatial learning ability compared with the control group, which was consistent with the pathological changes. In addition, rifampicin significantly elevated the nuclear expression of Nrf2, Nrf2 downstream anti-oxidant protein, HO-1 compared with the control group, and it simultaneously downregulated the expression of COX-2 in the hippocampus on day 3 after ischemia-reperfusion. Interestingly, the forenamed effects of rifampicin were abolished by pretreatment with brusatol, a specific inhibitor of Nrf2 activation. Conclusions: Rifampicin exerts neuroprotective effects against global cerebral ischemia, which may be attributed to activation of the Nrf2 pathway.